Fall Prevention: How to Handle a Fall - Leigh Nova; Linda Bobroff; Wendy Lynch (EDIS)
After a fall, panic is often the first reaction. It is important to stay calm and remain still so you can think clearly and take the appropriate steps to get help if needed.